Engglish Pilgrimage Tradition And The Strengthening Of Spiritual Intelligence Among GP Ansor Cadres In Bojong - Aris Priyanto; Muhammad Mufid (Journal of Sufism and Psychotherapy, 2026)
This study was motivated by the mindset of the people of Bojong, who do not sufficiently appreciate the struggles of the ulama who carried out the process of Islamization in the Bojong region. Although their role was immense, the ulama did not merely teach religious doctrine but also imparted lessons on morality, character, and ethics that are useful in daily life. Thus, pilgrimages and tracing the footsteps of the ulama’s struggles serve as a means to emulate and draw lessons from their struggles, which can strengthen the spiritual intelligence of the cadres of the Ansor Youth Movement in Bojong. This study aims to examine the implementation of pilgrimages and the tracing of the ulama’s struggles as a means to enhance spiritual intelligence and the forms of spiritual intelligence among GP Ansor cadres in Bojong Subdistrict. This study is a field study employing a religious phenomenological approach, specifically examining the phenomenon of retracing the footsteps of the ulama in Bojong. Data were collected through interviews, observations, documentation, and sources such as books, academic articles, and other materials. The results of this study indicate that pilgrimages and the tracing of the ulama’s struggle are organized by the GP Ansor Bojong on every Islamic holiday, attended by all GP Ansor Bojong members. Meanwhile, the form of spiritual intelligence resulting from these pilgrimages and the tracing of the struggle of Bojong’s ulama is that GP Ansor Bojong members can emulate and follow the spirit of past ulama in spreading Islam in Bojong, accompanied by spiritual strengthening such as patience, trust, honesty, perseverance, as well as possessing noble character and engaging in specific devotional practices (dhikr) to nurture the inner spiritual dimension (ruhaniah).